Flipped Well-Plate Hanging-Drop Technique for Growing Three-Dimensional Tumors - Jeong, Yoon; Tin, Ashley; Irudayaraj, Joseph (Frontiers in Bioengineering and Biotechnology, 2022)
Three-dimensional (3D) tumor culture techniques are gaining popularity as in vitro models of tumoral tissue analogues. Despite the widespread interest, need, and present-day effort, most of the 3D tumor culturing methodologies have not gone beyond the inventors’ laboratories. This, in turn, limits their applicability and standardization. In this study we introduce a straightforward and user-friendly approach based on standard 96-well plates with basic amenities for growing 3D tumors in a scaffold-free/-based format. Hanging drop preparation can be easily employed by flipping a universal 96-well-plate. The droplets of the medium generated by the well-plate-flip (WPF) method can be easily modified to address various mechanisms and processes in cell biology, including cancer. To demonstrate the applicability and practicality of the conceived approach, we utilized human colorectal carcinoma cells (HCT116) to first show the generation of large scaffold-free 3D tumor spheroids over 1.5 millimeters in diameter in single well plates. As a proof-of-concept, we also demonstrate matrix-assisted tumor culture techniques in advancing the broader use of 3D culture systems. The conceptualized WPF approach will be adapted for a range of applications in both basic and applied biological/engineering research.